Elemen-elemen Sistem Manajemen Lingkungan Keselamatan dan Kesehatan Kerja (SMLK3) untuk Bisnis Berkelanjutan - Mastika Wardhani; Budi Suharjo; Setiadi Djohar (School of Business, Bogor Agricultural University (SB-IPB), 2018)
This study aimed to analyze the relationship among the elements of management commitment, operational controls and human resource competencies in the occupational environmental, safety, and health management systems (ESHMS) in the XYZ Group. The secondary data were obtained from the company archives and judgmental sampling was used against the 100 expert respondents to obtain the primary data. Descriptive analysis and structural equation modelling (SEM) were used for data analysis method. The results showed that management commitment element significantly influences the company operational control and human resource competencies, and the operational control elements significantly influences the human resource competencies.Keywords: ESHMS, management commitment, operational controls and human resource competencies, SEM